Prevalence of Gastrointestinal Nematodes in Local Indonesian Sheep Based on Rearing Systems and Animal Age - Somanjaya, Rachmat; Imanudin, Oki; Mutaqin, Bambang Cholik; Taruna, Rafi (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
This study aimed to evaluate the prevalence of gastrointestinal nematodes (GIN) in local Indonesian sheep based on the rearing system and animal age. Fecal samples were taken transrectally from lamb (<8 months) and adult sheep (>1 year), which were reared intensively and semi-intensively, each with a total of 25 samples. Furthermore, the fecal samples were processed using the floating method with a saturated salt solution (NaCl). Fecal Egg Counting (FEC), larvae, and nematode types were carried out microscopically in the Universal Whitlock counting chamber. The general linear model (GLM) analyzed the data with 95% confidence and continued with Tukey's test if interactions between factors were found. The results showed that the rearing system or age of the sheep did not have a significant influence and did not show an interaction (p>0.05) on the FEC. However, the average FEC of sheep reared semi-intensively, both in lambs and adult sheep, respectively, tended to be higher than in those reared intensively (898.75±280.36 vs 469.09±120.40 and 692.50±220.57 vs 513.00±106.88). It can be concluded that the semi-intensive rearing system and lambs are more susceptible to Gastrointestinal Nematode (GIN) infections if they are not accompanied by good rearing management, and the dominant type of worm found in sheep feces is Strongyloides spp.